PRODUCTION OF Bacillus thuringiensis BIOPESTICIDE USING COMMERCIAL LAB MEDIUM AND AGRICULTURAL BY-PRODUCTS AS NUTRIENT SOURCES - VALICENTE, FERNANDO HERCOS; TUELHER, EDMAR DE SOUZA; LEITE, MARIA ISABELLA SANTOS LEITE; FREIRE, FERNANDA LYON; VIEIRA, CORINA MACEDO (International Journal of Maize & Sorghum, 2010)
Bacillus thuringiensis (Bt) is a Gram-positive bacterium naturally found in soil, water and grain dust, and can be cultivated in liquid, solid and semi-solid media. The objective of this work was to test different media to grow B. thuringiensis. The seed culture (strain 344, B. thuringiensis tolworthi, belonging to Embrapa Maize and Sorghum Microorganism Bank) was produced using shake flasks and grown in LB medium plus salts during 18 hours, incubated on a rotary shaker at 200 revolutions per minute (rpm) at 30°C for 96 hours. Medium 1 was composed of: Luria Bertani (LB) plus salts (FeSO4, ZnSO4, MnSO4, MgSO4), and 0.2% glucose; medium 2 was composed of 1.5% glucose, 0.5% soybean flour plus salts; and medium 3 was composed of liquid swine manure at 4% and 0.2% glucose. All three media were sterilized and inoculated with B. thuringiensis tolwothi (seed culture) at a stirrer speed of 200rpm, for 96 hours at 30°C. The pH was measured at regular intervals, viable spores were counted as c.f.u/mL, cell mass expressed in g/L- lyophilized, and spore counting per mL of medium. All three media showed pH variation during the fermentation process. Media 1 and 2 showed a tendency to shift toward a basic pH and medium 3 to an acidic pH. Media 1 and 2 showed the highest number of viable spores, 2.0 x 108 c.f.u/mL, within the 96 hours of incubation, however medium 2 showed a biomass dry weight of 1.18g/L. During the fermentation period, medium 1 showed the highest spore concentration, 1.4 x 109 spores/mL after 96h of fermentation. Efficiency against S. frugiperda first instar larvae showed that all Bt produced in all three media killed above 60% in the highest concentrations.